Article review of “what it takes to be a manager: the case of Malaysian five star resort hotels” by Rozila Ahmad and Noor Azimin Zainol / Wan Nazriah Wan Nawawi and Gopala Krishnan Sekharan Nair - Wan Nawawi, Wan Nazriah; Sekharan Nair, Gopala Kishnan (2013)
Tourism is among the main contributor for the economic growth and its alignment with hotel industry has created many job opportunities to the local population. This has led to the continuous growth of public and private institutions offering hotel management courses to fill the workforce needs of these hotels. Despite the increasing number of hotel graduates, hotels are still facing worker shortages (Malaysian Association of Hotels, 2011b). The shortage of skilled workers in Malaysian hotels is caused by the unattractive work atmosphere of the industry. On the other hand it is caused by Malaysian workforce perception that it is difficult to get promotion and attain management positions in the hotel industry. Similar to the developed countries, Hotels in Malaysia are facing problems in attracting and retaining skilled and knowledgeable workers due to low salary, rigid job traits and conventional style of top-down operation (Ahmad, Solnet & Scott, 2010; Yamashita & Uenoyama, 2006; Davidson, Guilding & Timo, 2006). Numerous academic literatures in Malaysia have discussed on how the industry can retain their skilled employees. However, literature on how academicians can increase their students’ employability for management position is scarce despite the indication of Malaysian workforce inferiority to attain management position.